Peningkatan Kemampuan Guru Bahasa Inggris KKM MAN 1 Malang Dalam Menyusun Butir Soal Pilihan Ganda Melalui Collaborative Assistence - Yanto, Widayanto Wido (Inovasi: Jurnal Diklat Keagamaan, 2020)
The purpose of this study is to describe whether Collaborative Assistance can improve the ability of English teachers in compiling multiple choice questions. This study uses a qualitative research method with a school action research approach because this research was carried out based on the findings of problems in the field. The study was conducted in 2 cycles. The results obtained were an increase in the ability of English teachers in compiling multiple choice questions. The results of cycle 1, the average score of 84 and the results of cycle 2 increased by 94.